The advertising function of cookies: prevention and precautionary mechanisms in Spanish Law - Flaquer Riutort, Juan (2021)
The Internet increasingly radiates its essentialness in relationships, and in the different areas and activities of people. However, as we make a greater use of it, we expose our personal data to be stored and processed by third parties for commercial purposes. This is made possible by a tool that is present in most of the websites we browse on a daily basis: cookies.In this article, the author assesses the risks involved in the use of cookies for advertising purposes without an adequate legal framework. Furthermore, he analyzes the prevention and  precautionary mechanisms to follow in order to ensure a balance that respects the rights of users.